ANALISIS FAKTOR âFAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN PERUSAHAAN - Andhika Putri Pratiwi, 09.05.52.0149; Nurhayati, Ida (Students Journal of Accounting and Banking, 2013)
This research was conducted to analyze influence of company size (size), liquidity, leverage, and profitability. this Object Research at Manufacturing Company which listed in the Indonesia Stock Exchange (BEI) in 2010-2011 using the total sample of 66 companies per year. Data analysis techniques in this research use multiple linear regressions with the least squares equation and hypotheses test using the T-statistic for testing the partial regression coefficients and F-statistics to test the effect of independent variables on the dependent variable simultaneously. Under normality test, multicollinearity test, heteroscedasticity test and autocorrelation test in classic assumption donât be found by variable which digressing, and during the observation period of the research showed that the data were normally distributed. This shows the available data has been qualified using multiple linear regression equation models. The results of this research indicate that of company size (size), liquidity, leverage shows a significant influence on widespread voluntary disclosure. Meanwhile, profitability variable does not significantly effect on the profitability of extensive voluntary disclosure. Predictive ability of the four variables of the extensive voluntary disclosure in this research of 23.9% while the remaining 76.1% influenced by other factors not included in the research model. Keywords: company size (size), Liquidity, Leverage, Profitability, voluntary disclosure.